Cinnamate-amine hybrids: Antituberculosis activity and molecular docking - Nur Pasca Aijijiyah, Reni Rahayu, Alfatchu Srilistiani, Farah Mahzumi, Tinezsia Aulia, Liangga Santoso, Lukman Atmaja, Eko Santoso, Arif Fadlan, Mardi Santoso (Journal of Applied Pharmaceutical Science, 2024)
Antituberculosis activity and molecular docking experiments were performed on 14 cinnamate-amine hybrids. Cinnamamides 1a,b,c,d,i,j effectively inhibited the growth of Mycobacterium tuberculosis H37Rv, with cinnamamide 1c having the highest inhibition effects with a minimum inhibitory concentration value of 3.13 μg/ml. Based on the docking results, the molecule of cinnamamide 1c (binding energy of −4.13 kcal/mol) was found to be stretched from the edge of the active site to its sub-binding pocket, referred to as an extended conformation when binding to the InhA active site. Cinnamamide 1c turned out to be an inhibitor whose potency is unaffected by the conserved interaction network with the catalytic residue Tyr158. These findings suggest these cinnamate-amine hybrids as potential lead compounds in developing new antituberculosis drugs.
Keywords: Cinnamamide, molecular docking, antituberculosis activity, InhA inhibitor